2008
DOI: 10.1172/jci30473
|View full text |Cite
|
Sign up to set email alerts
|

Inherited human cPLA2α deficiency is associated with impaired eicosanoid biosynthesis, small intestinal ulceration, and platelet dysfunction

Abstract: Cytosolic phospholipase A 2α (cPLA 2α ) hydrolyzes arachidonic acid from cellular membrane phospholipids, thereby providing enzymatic substrates for the synthesis of eicosanoids, such as prostaglandins and leukotrienes. Considerable understanding of cPLA 2α function has been derived from investigations of the enzyme and from cPLA 2α -null mice, but knowledge of discrete roles for this enzyme in humans is limited. We investigated a patient hypothesized to have an inherited prostanoid biosynthesis deficiency due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
101
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 57 publications
10
101
1
2
Order By: Relevance
“…In one subject, two rare heterozygous single bp mutations in PLA2G4A were found; one mutation (S111P) occurred in the C2 domain of cPLA 2 ␣ and the other allele had a mutation in the catalytic domain (R485H) ( Fig. 2 ) ( 49 ). The expression of cPLA 2 ␣ protein and PLA 2 activity in platelet lysates was reduced compared with normals.…”
Section: Downloaded Frommentioning
confidence: 95%
See 2 more Smart Citations
“…In one subject, two rare heterozygous single bp mutations in PLA2G4A were found; one mutation (S111P) occurred in the C2 domain of cPLA 2 ␣ and the other allele had a mutation in the catalytic domain (R485H) ( Fig. 2 ) ( 49 ). The expression of cPLA 2 ␣ protein and PLA 2 activity in platelet lysates was reduced compared with normals.…”
Section: Downloaded Frommentioning
confidence: 95%
“…The consequences of inherited cPLA 2 ␣ defi ciency in several human patients have now been described (49)(50)(51). against colon cancer in mice induced by the colon carcinogen, azoxymethane, which induces increased tumor multiplicity in heterozygous and KO mice compared with WT mice ( 131 ).…”
Section: Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of these inhibitors have been used for in vivo animal models of inflammation and have shown potency in reducing inflammatory effects (40,41). Potential side effects of GIVA PLA 2 inhibitors have been suggested by recent work examining a human patient with defects in GIVA PLA 2 who showed decreases in PLA 2 activity, eicosanoid biosynthesis, and the generation of many small intestinal ulcers (42).…”
Section: Secreted Plamentioning
confidence: 99%
“…Bonventre et al (18) and Uozumi et al (19) independently demonstrated that peritoneal macrophages from Group IVA PLA 2 knockout mice were incapable of producing eicosanoids. More recently, Adler et al (20) identified a patient with inherited Group IVA deficiency and determined that nearly all arachidonic acid used for eicosanoid production by platelets and circulating leukocytes was attributable to this enzyme. The Group IVA cPLA 2 uses a catalytic Ser/Asp dyad to hydrolyze fatty acids and contains a C2 domain that facilitates calcium-dependent translocation from the cytosol to the membrane surface where it encounters phospholipid substrate.…”
Section: Phospholipase Amentioning
confidence: 99%